Nurses' Competence and Job Related Factors among Nurses in University Hospitals: A Cross Sectional Descriptive Design - Mobasher - Amini, Khadijeh; Rezaei, Behrooz; Esmaeilpour- Bandboni, Mohammad (Advances in Nursing & Midwifery, 2019)
Introduction: Nurses' Competence is a critical factor for providing safe and quality care and self- assessment is a key issue in maintenance of competence. This study was conducted to identify the level of competence and its associations with some job related factors. Methods: A cross sectional and descriptive design was conducted at seven university hospitals in Rasht during September 2015. This study included 230 nurses working in university hospitals who were selected using stratified sampling method. The majority of nurses was female and had a bachelor's degree. Nurses' competence was measured using self reported competency inventory for registered nurses (Persian version). Data was analyzed with Spearman correlation, Mann-Whitney-U SPSS /21 software. Results: The average score of competence was 173.59±26.72 and was considered in high level. The highest and the lowest competence were in dimensions of 'ethical-legal performance' (M=3.23±.52) and 'Critical thinking/research aptitude' (M=3.11±.51) respectively. There were significant associations between nurses' competence and some job related factors consisting work experience (p = 0.001), monthly salary (p = 0.001), working hours per month (p = 0.004), Nurses' shift work (p = 0.021), and employment type (p = 0.003). Conclusions: Nurses assessed their competence at a desirable level, which may be due to self-assessment tool. Some job related factors associated with nurses' competence. Exploring the competence level and its relationship with these factors could be helpful in managerial interventions for professional competency.